Effective n-octane isomerization under exceptionally mild conditions using a novel class of superacidic ionic liquids - Meyer, Carolin; Wasserscheid, Peter (Chemical Communications, 2010)
Superacidic chloroaluminate ionic liquids of the general formula [cation]Cl/AlCl(3)[X(AlCl(3)) > 0.5] + H(2)SO(4) effectively isomerize n-octane to form branched liquid hydrocarbon isomers. Due to the highly acidic character of the ionic liquid the reaction proceeds under extremely mild conditions in a liquid-liquid biphasic reaction mode leading to a minimum of undesired cracking side-reactions.